PENGARUH INTENSITAS PENDAMPINGAN, PENDANAAN DAN LITERASI KEUANGAN TERHADAP STATUS KEBERHASILAN PROSES INKUBASI TENANT INKUBATOR BISNIS - Puspita Yanti, Ni Putu Yayuk; Dewi, Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.08.TAHUN.2021DO - 10.24843/EEB.2021.v10.i08.p04, 2021)
The purpose of this study was to analyze the effect of the intensity of mentoring, funding, and financial literacy simultaneously and partially on the success status of the business incubator tenant incubation process in Bali Province. This study uses primary data by distributing questionnaires to 97 business incubator tenants in Bali Province. The analysis technique used is multiple linear regression which is equipped with a classical assumption test. The results of the test analysis in this study indicate that simultaneously the intensity of mentoring, funding, and financial literacy has a positive and significant effect on the success status of the business incubator tenant incubation process in Bali Province. Partially, the intensity of mentoring and financial literacy has a positive and significant effect on the success status of the business incubator tenant incubation process in Bali Province, while partially funding has a negative and significant effect on the success status of business incubator tenants in Bali Province. The government is expected to develop superior local products from upstream to downstream as the basis for cooperative business and MSME, strengthening the synergy and orchestration of cooperative and MSME-based people's economic development with all ministries and all business stakeholders.